2017
DOI: 10.1111/febs.14362
|View full text |Cite
|
Sign up to set email alerts
|

Shared CaM‐ and S100A1‐binding epitopes in the distal TRPM4 N terminus

Abstract: The transient receptor potential channel of melastatin 4 (TRPM4) belongs to a group of large ion receptors that are involved in countless cell signalling cascades. This unique member is ubiquitously expressed in many human tissues, especially in cardiomyocytes, where it plays an important role in cardiovascular processes. Transient receptor potential channels (TRPs) are usually constituted by intracellular N- and C- termini, which serve as mediators affecting allosteric modulation of channels, resulting in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(52 citation statements)
references
References 61 publications
1
47
0
Order By: Relevance
“…They are generally considered as relatively low specificity proteins, with dozens of interaction partners, among them they are unable to maintain a high selectivity [15]. In this study we determined the interaction profile of the full human S100 family (termed here as the S100ome) against a set of diverse known S100 partners (and some of their paralogs) systematically, including kinases such as RSK1 [16] and its paralogs MK2 and MNK1; cytoskeletal elements such as CapZ [17] (commonly known as TRTK12), NMIIA [18], ezrin [19], FOR20 and its paralog FOP [20]; membrane proteins such as NCX1 [15] and TRPM4 [21]; and other signaling proteins such as the tumor suppressor p53 [22][23][24], SIP [15] and MDM4 [23].…”
Section: Introductionmentioning
confidence: 99%
“…They are generally considered as relatively low specificity proteins, with dozens of interaction partners, among them they are unable to maintain a high selectivity [15]. In this study we determined the interaction profile of the full human S100 family (termed here as the S100ome) against a set of diverse known S100 partners (and some of their paralogs) systematically, including kinases such as RSK1 [16] and its paralogs MK2 and MNK1; cytoskeletal elements such as CapZ [17] (commonly known as TRTK12), NMIIA [18], ezrin [19], FOR20 and its paralog FOP [20]; membrane proteins such as NCX1 [15] and TRPM4 [21]; and other signaling proteins such as the tumor suppressor p53 [22][23][24], SIP [15] and MDM4 [23].…”
Section: Introductionmentioning
confidence: 99%
“…The FA increased due to a slower rotational diffusion of the formed complexes, and the fraction bound (F b ) of M4nt_WT and M4ct_WT could be calculated ( Figure 2 A, Figure 3 A, Figure 4 A, Figure 5 A). Since the specific interactions of M4nt_WT and M4ct_WT with CaM/S100A1 were calcium-dependent [ 36 , 37 , 38 , 39 , 40 ], all samples were measured in the presence of 200-μM CaCl 2 . The fluorescence lifetimes τ i of all peptides and their complexes (and all the following characterised peptides/complexes) were constant during all the experiments, with the values close to 3 ns.…”
Section: Resultsmentioning
confidence: 99%
“…The most reasonable complex identified by the ClusPro protein–protein docking process revealed that the M4nt_WT peptide was bound to the main binding site of S100A1 [ 40 , 43 ]. During subsequent MD simulations, M4nt_WT retained the canonical alpha-helical conformation, and numerous stabilising salt bridges were established ( Figure 3 C–F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the C-terminal binding site of CaM can significantly reduce TRPM4 current amplitude and promote faster current decay. This suggests that the C-terminal binding site of CaM is vital for the Ca 2+ sensitivity of TRPM4 [ 8 , 75 ].…”
Section: Physiological Characteristics Of Trpm4mentioning
confidence: 99%